The influence of corporate governance on company financial performance in the financial sector - Muhammad Ifaz Padilatul Hamdi; Agus Munandar (Institute of Computer Science (IOCS), 2023)
Every company definitely wants the company it manages or owns to have good and correct governance, because every organization wants this to create the governance they want. So here the role of corporate governance becomes important with the variables Board independence, audit committee, institutional ownership, board size and the number of board meetings in a company which can lead to comfort and protection for shareholders and investors, governance adopted in controlling an organization it will direct the policies or steps of an organization, so that the goal to be achieved in this study is to provide an explanation of the influence of board independence, audit committees, institutional ownership, number of board meetings and board size on company financial performance with the research method of panel data regression analysis and research This was carried out on 36 companies in the financial sector listed on the Indonesia Stock Exchange (IDX) from the 2017 period to the 2021 period and produced a simultaneous test that board independence, board size, audit committee, institutional ownership and number of board meetings jointly have an effect on financial performance with the control variables firm size and leverage while the results partially board independence, board size have a positive and significant effect while the audit committee and institutional ownership and the number of meetings have no effect on financial performance